2022
DOI: 10.3390/molecules27144553
|View full text |Cite|
|
Sign up to set email alerts
|

Hyaluronic Acid Modified Nanostructured Lipid Carrier for Targeting Delivery of Kaempferol to NSCLC: Preparation, Optimization, Characterization, and Performance Evaluation In Vitro

Abstract: Lung cancer seriously threatens the health of human beings, with non-small cell lung cancer (NSCLC) accounting for 80%. Nowadays, the potential position of nano-delivery in treating cancer has been the subject of continuous research. The present research aimed to prepare two molecular weight hyaluronic acid (HA)-modified kaempferol (KA)-loaded nanostructured lipid carriers (HA-KA-NLCs) by the method of melting ultrasonic and electrostatic adsorption, and to assess the antitumor effect of the preparations on A5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Twelve of the studies included in this systematic review explored the role of cellular toxicity of KMP in lung cancer cells using A549 [22,44,[47][48][49]53,70,73,80] or H460 cells [27,60,61]. The findings were consistent, indicating a strong cytotoxicity of KMP.…”
Section: Kmp Inhibits Cell Proliferation Invasion and Migration And P...mentioning
confidence: 86%
See 1 more Smart Citation
“…Twelve of the studies included in this systematic review explored the role of cellular toxicity of KMP in lung cancer cells using A549 [22,44,[47][48][49]53,70,73,80] or H460 cells [27,60,61]. The findings were consistent, indicating a strong cytotoxicity of KMP.…”
Section: Kmp Inhibits Cell Proliferation Invasion and Migration And P...mentioning
confidence: 86%
“…Table 1 shows the main findings according to type of tumor. Most of the studies included in the present review explored the effects of KMP on tumor cell death [10,12,22,[27][28][29][30][31][32]35,36,40,46,[51][52][53][55][56][57]62,63,66,70,[74][75][76][77]80,81]. These studies reported the apoptosis-inducing properties of KMP, which can be partially attributed to its impacts on the MAPK pathway.…”
Section: Kmp Inhibits Cell Proliferation Invasion and Migration And P...mentioning
confidence: 99%
“…These hydroxyls are also able to chelate metal ions and, thus, hamper the metal-catalyzed generation of reactive oxygen substances (ROS) and their oxidant activity. According to our research of the literature, the flavonoids that have been included in HA-coated delivery nanosystems investigated against cancer in the last 5 years are the two flavonols: kaempferol [34] and quercetin (QU) [35][36][37][38][39][40][41], the flavanol epigallocatechin-3-gallate (EGCG) [42][43][44][45][46][47] the flavanone naringenin [48], the isoflavone formononetin [49], and a mix of anthocyanins extracted from corn [50]. Between brackets are reported the number of compounds belonging to each class or subclass according to this classification.…”
Section: Phecs Included In Drug Nanodelivery Systems For Tumor Targetingmentioning
confidence: 99%
“…Kaempferol, another flavonol, was recently encapsulated in a HA-modified nanostructured lipid carrier for the therapy of lung cancer [ 34 ]. The authors constructed two NPs and tested them against A549 lung carcinoma cells.…”
Section: Newly Developed Ha-based Nanocarrier Systems Loading Phecs A...mentioning
confidence: 99%
“…Among the natural polymers, chitosan, pectin, alginate, starch and dextran are used to prepare microparticles loaded with different drugs to treat periodontal diseases [ 4 , 5 , 6 ]. Another important polysaccharide, hyaluronic acid, which is used in the cosmetic industry, prepares the scaffold for tissue engineering for drug delivery, disease diagnoses and biomedical imaging; it represents an ideal candidate to obtain polymeric materials for the dental field [ 7 , 8 , 9 , 10 ]. The use of polymeric microparticles in dentistry has been increasing due to the excellent properties of both polymeric materials (good surface, biological and mechanical properties, low manufacturing cost, simple synthesis methods) as well as of microparticles (high surface/volume ratio, good accessibility to the site of action due to their size, stability in biological fluids, drug transport capacity, decreased frequency and intensity of adverse effects) [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%